Implementasi Pajak Penghasilan Karena Warisan Dari Harta Bersama Yang Berkeadilan - Imron Chumaidi (Jurnal JURISTIC, 2025)
Taxes are an important instrument in national development that must reflect the values of justice as enshrined in Pancasila. However, in the practice of taxation on inherited communal land, issues of unfairness arise for substitute heirs (second-degree heirs) who are subject to a 5% Income Tax (PPh), while first-degree heirs are exempted through a Certificate of Exemption (SKB) mechanism. This regulation raises legal and ethical problems because it is not in line with the principle of substantive justice in Indonesian inheritance law and tax law. This study formulates two main questions, namely: (1) what are the applicable legal provisions regarding the imposition of income tax on the transfer of rights to land due to inheritance in the form of communal rights to substitute heirs, and (2) whether the implementation of these tax provisions reflects the principle of justice according to the values of Pancasila and the principles of Indonesian tax law. This study uses a juridical-normative approach with a constructivist paradigm. Data were obtained through a literature study of legislation, legal doctrines, as well as case studies from field practices, including interviews with taxation stakeholders. A dialectical hermeneutic method was used to examine the relationship between legal norms and social reality. The results show that, normatively, inheritance is excluded from the tax object as regulated in Article 4 paragraph (3) letter b of the Income Tax Law. However, in practice, this exemption does not apply to substitute heirs due to an administrative interpretation that limits the Certificate of Exemption (SKB) to first-degree heirs only. This creates legal uncertainty, discrimination in tax services, and contradicts the principle of justice in Pancasila. Therefore, a reformulation of administrative regulations is needed to be more inclusive, fair, and ensure legal certainty for all heirs without discrimination.